(untitled) - Breytenbach, Jacomi Heidi

Exploring the interactions of hyperglycaemia, SARS-CoV-2 spike protein & iron in HepG2 cells (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.